Hematopoietic Stem Cell Transplantation Resolves the Immune Deficit Associated with STAT3-Dominant-Negative Hyper-IgE Syndrome - Harrison, Stephanie C. (J Clin Immunol, 2021)
Autosomal dominant hyper-IgE syndrome caused by dominant-negative loss-of-function mutations in signal transducer and activator of transcription factor 3 (STAT3) (STAT3-HIES) is a rare primary immunodeficiency with multisystem pathology. The quality of life in patients with STAT3-HIES is determined by not only the progressive, life-limiting pulmonary disease, but also significant skin disease including recurrent infections and abscesses requiring surgery. Our early report indicated that hematopoietic stem cell transplantation might not be effective in patients with STAT3-HIES, although a few subsequent reports have reported successful outcomes. We update on progress of our patient now with over 18 years of follow-up and report on an additional seven cases, all of whom have survived despite demonstrating significant disease-related pathology prior to transplant. We conclude that effective cure of the immunological aspects of the disease and stabilization of even severe lung involvement may be achieved by allogeneic hematopoietic stem cell transplantation. Recurrent skin infections and abscesses may be abolished. Donor T(H)17 cells may produce comparable levels of IL17A to healthy controls. The future challenge will be to determine which patients should best be offered this treatment and at what point in their disease history.